Neck and mind: exploring emotion processing in cervical dystonia - Carbone, Federico; Peball, Marina; Ellmerer, Philipp; Heim, Beatrice; Nachbauer, Wolfgang; Indelicato, Elisabetta; Amprosi, Matthias; Mahlknecht, Philipp; Hussl, Anna; Hotter, Anna; Granata, Roberta; Seppi, Klaus; et al. (Frontiers in neuroscience, 2025)
A wide range of non-motor symptoms such as pain, mood disorders, insomnia, and executive dysfunction may occur in focal dystonia. Little is known, however, about emotional processing. We aim to assess emotion recognition and alexithymia in patients with cervical dystonia (CD) compared to healthy age-, sex- and education-matched controls (HC). Emotion processing was assessed with an eye-tracking paradigm using a validated dataset of facial expressions and the Toronto Alexithymia Scale (TAS-20). Dystonia severity and disability, cognition, and comorbid depression and anxiety were also assessed. We recruited 35 CD patients and 17 matched HC. In the eye-tracking task, CD patients recognized emotions less accurately than HCs (77.0% vs. 84.4%; = 0.001), primarily based on difficulties in identification of fear ( = 0.003) and surprise ( = 0.037). Moreover, patients had longer fixations within the mouth region ( = 0.027) and left eye ( = 0.037) than HC. CD patients also had significantly higher total TAS-20 scores ( = 0.002) and subscores (difficulty identifying and describing feelings; all ≤ 0.026). Five patients (14.3%) reached the threshold for alexithymia and 6 (17.1%) for possible alexithymia. No HC scored positive for alexithymia and only 2 (11.8%) did for possible alexithymia. TAS-20 score correlated inversely with emotion recognition task performance ( = -0.411; = 0.014). We found poorer performance in emotion recognition in CD patients compared to HC. Together with a different gaze pattern and higher scores for alexithymia our results highlight deficits in emotion processing in CD.